Bioactivity of Gold Nanoparticles Synthesized from Lion's Mushroom on Multidrug-Resistant (MDR) ESKAPE Bacterial Isolates - Ammar Hatem Sultan; Reyam F. Saleh (Tikrit Journal of Pure Science)
The current study aims is to evaluate the antibacterial activity of gold nanoparticles manufactured using the green method from aqueous extract of lion's mane fungus against multidrug-resistant (MDR) ESKAPE group isolates, which included Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter baumannii, Enterococcus faecalis, Escherichia coli, and klebsiella pneumoniae. Antibiotic resistance is one of the biggest threats to public health around the world, and to treat this, many therapeutic alternatives are being used, including the use of nanotechnology to create nanoparticles. During this study, isolates from the ESKAPE group were diagnosed and a sensitivity test to five antibiotics was performed, in addition to the synthesis of gold nanoparticles and their examination using several techniques, including an ultraviolet-visible spectroscopy device, an Fourier transmission infrared (FTIR) spectroscopy device, and a scanning electron microscope (SEM). And determine the inhibitory activity of nanoparticles against bacterial isolates. The green synthesis of gold nanoparticles (AuNPs) was accomplished using an aqueous extract of lion's mane mushroom. Tests confirmed that the formed particles have high absorbance at a wavelength of (540 nm). It was observed using a scanning electron microscope that the nanoparticles are spherical in shape and with nano sizes ranging from (20.77 to 29.37 nm). As for the FTIR examination, the range is between (447.49 cm-1 - 3398.57 cm-1). The results of the current study showed that the biosynthesized AuNPs possess antibacterial activity against ESKAPE group isolates, with inhibition diameters ranging from (9 mm – 21 mm).